2015-2017‫ﺗﺤﻠﻴﻞ‬‫ﻇﺎﻫﺮة‬ ‫اﻟﻔﺸﻞ‬ ‫اﻟﻤﺎﻟﻲ‬ ‫ﻓﻲ‬ ‫اﻟﻤﺆﺳﺴﺔ‬ ‫اﻹﻗﺘ‬ ‫ﺼﺎدﻳﺔ‬‫واﻟﺒﺪاﺋﻞ‬ ‫اﻟﻤﺘﺎﺣﺔ‬ ‫ﻟﻤﻮاﺟﻬﺘﻪ‬ ‫دراﺳﺔ‬ ‫ﺣﺎﻟﺔ‬‫اﻟﻤﺆﺳﺴﺔ‬ ‫اﻟﻮﻃﻨﻴﺔ‬ ‫ﻟﻠﺪﻫﻦ‬ ‫وﺣﺪة‬ ‫ﺳﻮق‬ ‫أﻫﺮاس‬ ‫ﺧﻼل‬ ‫اﻟﻔﺘﺮة‬ ‫‪:‬‬‫ - ‬‫إﻛﺮام‫ ﺳﻠﻴﻤﺎﻧﻲ ‬; ‫ﺧﻮﻟﺔ‫ ﺑﻠﺨﻴﺮ‬‬ (My University, 2019)
This study aims at analysing the phenomenon of financial failure which would lead the institution to fail or disappear .this dessertation sheds the light on the theoritical and parctical aspects of financial failure . Through setting the concepts and theoritical foundations of this phenomenon , moreover ,it attempts to find solutions to the failure of the institution by setting alternatives that could be available to institution in order to encounter the danger of the financial failure . The practical aspect of this work depends on studying the case of the national institution of painting during the period of 2015 to 2017,therefore ,it has been used a set of financial diagnostic tools such as indicators and financial ratios. Also ,it has been used some quentity models as "beaver,kids, and sherrord" which include a set of financial ratios that could forecast the financial failure. This study reveals that the financial status of the case institution is good, and that two models ; kids and sherrord had the ability to reveal the exact status of thwe institution . Also , I find that the financial status of the latter match with the two models . Key words : financial failure , forecasting ,diagnosis ,cure